Long-Acting Muscarinic Antagonists Under Investigational to Treat Chronic Obstructive Pulmonary Disease - Ora J; Coppola A; Cazzola M; Calzetta L; Rogliani P (Dove Medical Press, 2020)
Josuel Ora,1 Angelo Coppola,2 Mario Cazzola,3 Luigino Calzetta,4 Paola Rogliani1,3 1Division of Respiratory Medicine, University Hospital Tor Vergata, Rome, Italy; 2Division of Respiratory Medicine, San Filippo Neri Hospital, Rome, Italy; 3Department of Experimental Medicine, University of Rome Tor Vergata, Rome, Italy; 4Department of Medicine and Surgery, Respiratory Disease and Lung Function Unit, University of Parma, Parma, ItalyCorrespondence: Josuel OraDivision of Respiratory Medicine, University Hospital Tor Vergata, Viale Oxford 81, Rome 00133, ItalyEmail josuel.ora@ptvonline.itIntroduction: Bronchodilators are the cornerstone of chronic obstructive pulmonary disease (COPD) therapy and long-acting muscarinic antagonists (LAMAs) as a mono or combination treatment play a pivotal role. Several LAMAs are already available on the market in different formulations, but developing a new compound with a higher M3 receptor selectivity and a lower affinity to M2 receptors to increase the therapeutic effect and minimize the adverse effects is still a goal. Moreover, new formulations could improve adherence to therapy.Areas Covered: This systematic review assesses investigational long-acting muscarinic antagonist in Phase I and II clinical trials over the last decade. It offers insights on whether LAMAs and/or their new formulations in clinical development can become effective treatments for COPD in the future.Expert Opinion: Research on LAMA seems to have come to a standstill, the few new molecules under study do not show distinctive characteristics compared to the previous ones. Muscarinic antagonist/β 2-agonist (MABAs) appear to be the major innovation currently under investigation, and they could theoretically open new research frontiers on the effect between adrenergic and muscarinic interaction in the same cell.Keywords: long-acting muscarinic antagonist, MABA, LAMA, Phase I, Phase II, efficacy, safety, COPD treatment, investigational drugs, chronic obstructive pulmonary disease